Ethics and Technology Transfer: Patients, Patents, and Public Trust. (1st June 2011) - Zucker, Deborah
Abstract : Universities and academic medical centers have been increasing their focus on technology transfer and research commercialization. With this shift in focus, academic-industry ties have become prevalent. These relationships can benefit academic researchers and help then to transform their research into tangible societal benefits. However, there also are concerns that these ties and the greater academic focus on commercialization might lead to conflicts of interest, especially financial conflicts of interest. This paper briefly explores some of these conflicts of interest, particularly relating to research and training. This paper also discusses some of the policies that have been, and are being, developed to try to mitigate and manage these conflicts so that academic involvement in technology transfer and commercialization can continue without jeopardizing academic work or the public's trust in them.